Corrupção e o valor das firmas - Teixeira, Ester Medley Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
The present study proposes to analyze the corruption effects on the value of firms in different institutional environments, which offer different levels of exposure to bureaucracy, excessive regulations and other failures. For this, both the linear regression technique and the quantile regression were used. The last one allows the sample distribution in compound groups from the companies with the lowest market value to those with the highest value. The results pointed to a heterogeneous effect on the behavior of variables, indicating that a reduction in the exposure to corruption risk negatively impacts the lower value companies, and positively on higher value firms. The comparative analysis with the results obtained from the conventional regression showed that its use may be insufficient to represent this phenomenon in a representative way. Therefore, we consider the contribution of this study relevant to this subject research, providing evidence corroborating the idea that the "grease" and "sand" hypotheses in the gear do not contradict each other, but complement each other and are possible in different contexts in which firms can be inserted
Keywords: Corrupção; Valor da firma; Ambiente institucional; Corruption; Firm value; Institutional environment; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA